EFFECT OF CYP19 GENE ON POLYCYSTIC OVARY SYNDROME PHENOTYPE IN IRAQI WOMEN (Iraqi Journal of Medical Sciences, 2016)
Background:Ovarian androgen overproduction is the key physiopathologic feature of polycystic ovary syndrome and the bulk of evidence points to the ovary being the source of excess androgens, which appears to result from an abnormal regulation (dysregulation) of steroidogenesis. Aromatase is an enzyme complex responsible for a key step in the biosynthesis of estrogen. It is encoded by CYP19.Objective:To examine whether the rs2414096 of CYP19 gene contributes to genetic susceptibility to the polycystic ovary syndrome hyperandrogenism in Iraqi women.Methods:A Case control study was conducted in the High Institute of Infertility Diagnosis and Assisted Reproductive Technologies, Al-Nahrain University and Al-Nahrain Forensic DNA Unit, Baghdad, Iraq for the period from February 2012 to February 2013. Sixty-five healthy women serves as the control group and eighty-four infertile women with polycystic ovary syndrome, divided into two subgroups depending on the body mass index (< and ?30 kg/m2) were studied. Restriction fragment length polymorphism analysis was performed to determine the genotypes of rs2414096 of CYP19. Clinical, anthropometric, hormonal and biochemical parameters were also estimated.Results: Genotypic distribution of rs2414096 of CYP19 was significantly different in polycystic ovary syndrome patients from that of control women. The frequency of GG genotype was higher in the patients, while AA genotype was higher in control women. Those with GG genotype have lower estradiol, estradiol/testosterone and higher testosterone, luteinizing hormone, follicular stimulating hormone than those with AA genotype.Conclusion:The present data suggests that single-nucleotide polymorphisms rs2414096 in the CYP19 gene is associated with susceptibility to polycystic ovary syndrome hyperandrogenism in Iraqi women.Keywords :Polycystic ovary syndrome, CYP19 gene, reproductive hormones, Iraqi women.
Keywords: Polycystic ovary syndrome; CYP19 gene; reproductive hormones; Iraqi women